The effects of timing of prophylaxis, type of anesthesia, and use of mechanical methods on outcome in major orthopedic surgery – subgroup analyses from 17,701 patients in the XAMOS study - Haas, Sylvia (Vasc Health Risk Manag, 2016)
PURPOSE: Real-world data on the use of rivaroxaban in the perioperative period in patients undergoing major orthopedic surgery are limited. Subsets of data from the Phase IV, non-interventional XAMOS study were analyzed to explore the potential influence of timing of the first thrombo prophylactic dose, type of anesthesia, and concomitant mechanical prophylaxis on clinical outcomes in patients undergoing major orthopedic surgery in routine clinical practice. PATIENTS AND METHODS: In XAMOS, 8,778 patients received rivaroxaban (10 mg once daily) and 8,635 received standard-of-care (SOC) pharmacological prophylaxis (safety population). Crude incidences of symptomatic thromboembolic and treatment-emergent bleeding events were analyzed according to timing of the first postoperative thromboprophylactic dose, use of general or neuraxial anesthesia, and use of mechanical prophylaxis with pharmacological thromboprophylaxis. RESULTS: In the rivaroxaban group, the incidences of symptomatic thromboembolic events were 0.7%, 1.0%, and 0.7% in patients receiving the first thromboprophylactic dose at ≤6 hours, >6 hours to ≤10 hours, and >10 hours to ≤24 hours after surgery, respectively. In the SOC group, the incidence of symptomatic thromboembolic events was slightly higher when the postoperative dose was given at >10 hours to ≤24 hours (1.8% vs 1.1% at ≤6 hours and 1.3% at >6 hours to ≤10 hours). The antithrombotic effect of rivaroxaban was maintained in comparison to the SOC group. The incidence of major bleeding (RECORD trial definition) was low and similar between the two treatment groups and was not influenced by timing of the first thromboprophylactic dose. Neuraxial anesthesia was used more than any other form of anesthesia for both hip and knee surgery; the effectiveness of rivaroxaban was not influenced by the type of anesthesia used. No spinal hematomas were reported in patients receiving neuraxial anesthesia in either treatment group. Use of mechanical thromboprophylaxis in addition to rivaroxaban or SOC pharmacological prophylaxis did not reduce the risk of thromboembolic events further. CONCLUSION: The effectiveness and safety of rivaroxaban in patients undergoing major orthopedic surgery in routine clinical practice were maintained irrespective of timing of the first postoperative dose within 24 hours after surgery, the type of anesthesia, and the additional use of mechanical thromboprophylaxis.